Theoretical approach model of building integrated photovoltaic thermal air collector - Ahmad Fudholi; Muhammad Zohri; Ivan Taslim; Merita Ayu Indrianti; Intan Noviantari Manyoe (Institute of Advanced Engineering and Science, 2020)
Over recent years the photovoltaic technology has obtained signiﬁcant development, especially in building integrated photovoltaic thermal (BIPVT) system. Photovoltaic thermal (PVT) air collectors are advantageous because of their efficiency. Various studies have been conducted to determine the ideal parameters of PVT air collectors. Few theoretical approach models of PVT air collector systems were used to help detect occurrences in a PVT collector system and calculate the optimal parameters. The heat transfer and energy balance of PVT air collectors were analysed and reviewed based on the model, quantity of cover, channels and forms of the collector. A mathematical model was developed to describe actual working situations and to examine new shut PVT collectors. The first law of thermodynamics is the principal equation in the model. Different analysis methods were utilised to evaluate PVT performances, which are generally based on energy and exergy analyses. This review focuses on theoretical approach model of single-pass PVT air collector.